Characters from the Diamond: Wild Events, Crazy Antics, and Unique Tales from Early Baseball - Waldo, Ronald T. (Rowman & Littlefield Publishers, 2016)
Baseball during the late 1800s and the Deadball Era was filled with aggressive, hard-nosed players who had no qualms about exhibiting belligerent behavior while tenaciously achieving victory on the diamond. These unique and eccentric individuals helped the game grow in popularity through their brilliance on the field and their legendary exploits off it. From manager Miller Huggins fighting with a pitcher over thick, juicy steaks to Rube Waddell getting arrested for tossing doughnuts at the coiffure of a waitress, their stories kept baseball fans entertained throughout the season—and still entertain us today. In Characters from the Diamond: Wild Events, Crazy Antics, and Unique Tales from Early Baseball, Ronald T. Waldochronicles the adventures of an unparalleled group of players, managers, and umpires whose tales continue to define that era of baseball. From the days of Chris Von der Ahe when his St. Louis Browns dominated the American Association to the Great War, this book presents an array of unique stories, peculiar accounts, and humorous anecdotes involving the men who were the very fabric of the game during that time period. Baseball icons such as John McGraw, Willie Keeler, Ty Cobb, Frank Chance, Rube Waddell, and Mike Donlin are profiled in this book, while numerous lesser-known players—including Arthur Evans, Jack Rowan, Bill Kellogg, Bill Bailey, Ping Bodie, and William Dugan—are also given their moment in the sun alongside their more famous baseball brethren. Characters from the Diamond breathes life back into baseball from the late nineteenth century and Deadball Era. Illuminating, entertaining, and noteworthy, these stories surrounding some of the game’s most unique individuals paint a humorous, off-beat picture of an often-forgotten era for baseball lovers everywhere.